Risalah Khoridatul Bahiyah Terhadap Ilmu Kalam Dalam Karangan Syekh Ad-Dhardiri - Faiqotul Himmah; Fatimatus Zahro; Muhammad Imamul Muttaqin (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
This research aims to critically reveal the science of kalam regarding the views of Sheikh Ahmad Ad-Dardiri, a Shufi scholar who has several works. Of his many works, the most popular among students is the book